Continuous Midwifery Care Reduces Mortality in Indonesia: Asuhan Kebidanan Berkesinambungan Menurunkan Angka Kematian di Indonesia - Gita, Prigi Dewi; Widowati, Hesty (Universitas Muhammadiyah Sidoarjo, 2024)
Continuity of Care (COC) in midwifery involves comprehensive care from pregnancy to postpartum and family planning to reduce maternal and infant mortality rates (MMR 4.6% and IMR 13.49%). This case study examines the midwifery care of Mrs. F, a 29-year-old multipara at 40 weeks gestation, at Klinik Rahman Rahim II from August 14, 2023, to October 14, 2023. The study used observational methods and found no complications or discrepancies from standard practices during prenatal visits, childbirth, postpartum, and newborn care. Mrs. F successfully used a three-month contraceptive injection without side effects. The study underscores the importance of continuous midwifery care to improve maternal and infant health outcomes. Highlight: Continous care reduces meternal and infant morality rates No complications observed with standard midwifery practices Effective family planning improves maternal health outcomes Keyword: Continuity of Care, Midwifery, Maternal Health, Infant Health, Family Planning